Pelatihan Pengolahan Jajanan Sehat berbasis Rumpul Laut dalam rangka Pencegahan Masalah Gizi Buruk di Kabupaten Kupang: Training on Processing Seaweed-based Healthy Snacks in the Context of Preventing Malnutrition Problems in Kupang Regency - Pellokila, Marthen Robinson; Picauly, Intje; Marni, Marni; Talahatu, Anna Henny (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Processed snacks are served in many places, in various types, and are very popular with various groups, including children under five. The snacks in question are traditional and manufactured drinks and processed foods. This service activity was carried out to increase the knowledge and skills of family mothers in choosing and processing healthy snacks for family members, including toddlers, in Tablolong Village, West Kupang District, Kupang Regency, on July 29, 2023, with 50 family mothers participating using the "Education and counseling and simulation.” Before the extension activities are carried out, pre and post-test evaluations will be carried out to measure the abilities and changes in attitudes and actions of the mothers participating in the training regarding the extension material. The pre-test results found that most (62.7%) of family mothers did not understand well healthy snacks (snacks) regarding the type, quantity, and correct method of processing food. However, after confirmation from the results of counseling and food processing simulations, it is known that 100% of family mothers already understand and can choose types of food, prepare simple but nutritious menus with processing methods that are friendly to the availability of sufficient and appropriate nutritional content that is needed and can ensure that the amount of food consumed is according to the needs per day per age per gender of family members.